2023
DOI: 10.14710/nmjn.v13i1.49860
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depression and Its Contributing Factors among Mothers during the COVID-19 Pandemic in North Jakarta, Indonesia

Venna Yaasmiin Aadillah,
Irma Nurbaeti

Abstract: Background: Postpartum depression is a common psychological problem that occurs after birth. It has become especially prevalent in the era of the COVID-19 pandemic. Several factors contribute to postpartum depression. However, a limited study evaluated factors contributing postpartum depression among mothers during the COVID-19 pandemic, particularly in Indonesia.Purpose: This study aimed to explore postpartum depression among mothers and its contributing factors during the COVID-19 pandemic.Methods: This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
1
2
1
Order By: Relevance
“…This could be attributed to cultural factors but was significantly correlated in the third month after childbirth when the family's involvement in supporting the mother after birth is prominent. This finding aligns with previous studies conducted in Indonesia (Aadillah & Nurbaeti, 2023 ; Nurbaeti et al, 2018 , 2019 ) but contradicts findings from studies in other countries (Easterbrooks et al, 2016 ; Falah-Hassani et al, 2016 ; Nilsen et al, 2013 ; Phipps et al, 2013 ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This could be attributed to cultural factors but was significantly correlated in the third month after childbirth when the family's involvement in supporting the mother after birth is prominent. This finding aligns with previous studies conducted in Indonesia (Aadillah & Nurbaeti, 2023 ; Nurbaeti et al, 2018 , 2019 ) but contradicts findings from studies in other countries (Easterbrooks et al, 2016 ; Falah-Hassani et al, 2016 ; Nilsen et al, 2013 ; Phipps et al, 2013 ).…”
Section: Discussionsupporting
confidence: 81%
“…This highlights the ongoing concern regarding mental health issues ((Falgas-Bague et al, 2023 ). The prevalence of postpartum depression in this study surpassed previous research conducted on postpartum mothers aged above 21 years (Aadillah & Nurbaeti, 2023 ; Nurbaeti et al, 2018 , 2019 ). Furthermore, the results align with a study conducted in the United States, suggesting that the rate of depression in adolescent mothers is higher than that in adult mothers during the postpartum period (Haroz et al, 2014 ).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Conversely, women who did not share utensils and tools during the pandemic were at a lower risk of infection ( 47 ). Another study suggested that factors such as advanced maternal age, childcare concerns, living conditions, lack of social support, dissatisfaction with marital relationships, and unintended pregnancy may contribute to the occurrence of postpartum depression during the COVID-19 pandemic ( 48 ).…”
Section: Discussionmentioning
confidence: 99%